Strategies in financial services, the shareholders and the system: Is bigger and broader better? - Ingo Walter (Hamburg Institute of International Economics (HWWA), 2002)
The financial services industry is ,,special“ in a variety of ways, including the fiduciary nature of the business, its role at the center of the payments and capital allocation process with all its static and dynamic implications for economic performance, and the systemic nature of problems that can arise in the industry. So the structure, conduct and performance of the industry has unusually important public interest dimensions. One facet of the discussion has focused on size of financial firms, however measured, and the range of activities conducted by them Is size positively related to total returns to shareholders? If so, does this involve gains in efficiency or transfers of wealth to shareholders from other constituencies, or maybe both? Does greater breadth generate sufficient information-cost and transaction-cost economies to be beneficial to shareholders and customers, or can it work against their interests in ways that may ultimately impede shareholder value as well? And is bigger and broader also safer? This paper starts with a simple strategic framework for thinking about these issues from the perspective of the management of financial firms. What should they be trying to do, and how does this relate to the issues of size and breadth? It then reviews the available evidence and reaches a set of tentative conclusions from what we know so far, both from a shareholder perspective and that of the financial system as a whole.
Keywords: G20; L10; 330; financial services; shareholders; size of financial firms; Finanzdienstleistung; Finanzsektor; Skalenertrag; Verbundvorteil; Kosten-Wirksamkeits-Analyse; X-Effizienz; Marktmacht; Diversifikation; Wertpapieranalyse; Shareholder Value; Vereinigte Staaten